2018
DOI: 10.15844/pedneurbriefs-32-10
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, the Ketogenic Diet and Epilepsy

Abstract: Investigators from the Department of Pediatric Neurology at the Children’s Hospital of Fudan University assessed the gut microbiome in pediatric patients with intractable non-lesional epilepsy who were treated with the ketogenic diet (KD) comparing differences between responders and non-responders over a period of 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…In general, increases in Firmicutes and Actinobacteria are seen in KD-responding children. Although, increases in Alistipes and Ruminococcaceae are apparent in nonresponders [319]. Similar patterns have been reported by authors investigating KD effects in animal models of epilepsy, with a positive effect being associated with changes in the composition of the microbiota associated with relative increases in levels of Akkermansia and Parabacteroides [231].…”
Section: Caveats and Uncertaintysupporting
confidence: 81%
See 1 more Smart Citation
“…In general, increases in Firmicutes and Actinobacteria are seen in KD-responding children. Although, increases in Alistipes and Ruminococcaceae are apparent in nonresponders [319]. Similar patterns have been reported by authors investigating KD effects in animal models of epilepsy, with a positive effect being associated with changes in the composition of the microbiota associated with relative increases in levels of Akkermansia and Parabacteroides [231].…”
Section: Caveats and Uncertaintysupporting
confidence: 81%
“…Although the data reviewed above suggest that BHB entry into the brain is a major driver of the therapeutic benefits of the KD or of KB supplements, it should be emphasized that other factors may be involved and the mechanisms underpinning such therapeutic benefits are not completely understood either in the case of epilepsy or otherwise. For example, several authors have reported profound changes in the composition of the microbiota following the administration of a KD in children with intractable epilepsy, which appear to be important if not essential for seizure control [231,319,320]. In general, increases in Firmicutes and Actinobacteria are seen in KD-responding children.…”
Section: Caveats and Uncertaintymentioning
confidence: 99%
“…In fact, mouse models of refractory epilepsy showed that those given antibiotics or reared in a germ-free environment were resistant to seizure protection from KD, while keto microbiota fecal transplant helped mice with seizure control. Therefore, these results support that keto microbiota is necessary to protect against seizures [32,40].…”
Section: Ketogenic Diet Keto Microbiota and Epilepsysupporting
confidence: 70%
“…However, little is known about the underlying mechanisms of action of KD. The most accepted hypotheses point out: metabolic changes, alteration of the signalling pathways, changes in the production of hormones and neurotransmitters, epigenetic modifications [22,24,27], and as would be expected, modulation of the microbiota [32].…”
Section: Modulation Of the Gut Microbiota Profilementioning
confidence: 99%
See 1 more Smart Citation